An approximate method for the ultimate shear strength of horizontally curved composite plate girders - Shanmugam, Nandivaram E.; Basher, Mohammed A.; Rashid, Khalim A. (Journal of Civil Engineering and Management, 2014)
The paper is concerned with the ultimate load capacity of horizontally curved composite plate girders. An approximate method to predict the ultimate shear strength of the girders is presented. The proposed method accounts for the tension field action in web panels, composite action between steel plate girder and reinforced concrete slab with full interaction and presence of web openings. The accuracy of the method is assessed by comparing the predicted values of ultimate shear strength with the corresponding results obtained by using the nonlinear finite element analyses through a computer package LUSAS. The comparisons show that the proposed method is capable of predicting the ultimate shear strength with an acceptable accuracy. Presence of web openings of different proportions and their effects on ultimate strength of the girders are examined. Girders with trapezoidally corrugated webs are also considered in the study.